Mesophase biosurfactant for increasing production and injection of oil field and preparation method of mesophase biosurfactant

By using mesophase biosurfactants prepared from combined materials such as composite surfactants in oilfield stimulation and pressure reduction and injection, the problems of low efficiency and poor stability in the existing technology have been solved, and oil production stimulation and pressure reduction and injection have been achieved. Coordination and improvement, and maintain stability in high-temperature acid corrosion environments.

CN119351072APending Publication Date: 2025-01-24TIANJIN JIAOEN ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411767332.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing biosurfactants are inefficient in oil fields in terms of increased production and pressure reduction and injection, and have poor stability in high-temperature acid-corrosion environments, making it difficult to achieve coordinated improvements in oil production and pressure reduction and injection.

Method used

The composite surfactant, the sibidine coupling agent, the vomiting temperature 80, the continuous tune agent and the graphene -based graphene -based graphene, mix and mix well through mechanical stirring to prepare a middle phase biological surface active agent.

Benefits of technology

The coordination and improvement of the product's oil collection production and the coordination of antihypertensive injection increase, and maintaining excellent stability in the environment of high temperature acid rot, which improves the efficiency of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169313880000121
    Figure BDA0005169313880000121
  • Figure BDA0005169313880000131
    Figure BDA0005169313880000131
  • Figure BDA0005169313880000141
    Figure BDA0005169313880000141
Patent Text Reader

Abstract

The invention relates to the technical field of surfactants, and particularly discloses an intermediate-phase biological surfactant for increasing production and injection of an oil field and a preparation method of the intermediate-phase biological surfactant. The intermediate-phase biological surfactant comprises the following raw materials in parts by weight: 15-20 parts of a composite surfactant, 5-8 parts of a continuous adjusting and feeding agent, 2-4 parts of a silane coupling agent, 1-3 parts of Tween 80, 3-6 parts of a graphene agent based on glass fiber modification and 20-25 parts of water. According to the biological surfactant, the composite surfactant is adopted to be matched with the silane coupling agent and the Tween 80, meanwhile, the continuous adjusting and feeding agent and the graphene agent based on glass fiber modification are added, and the composite surfactant and the graphene agent are matched and jointly synergized, so that the obtained surfactant can achieve coordinated improvement of oil extraction, yield increase, pressure reduction and injection increase of a product; meanwhile, the product has an excellent stability effect in a high-temperature acid corrosion environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surfactants, and in particular to a mesophase biosurfactant for increasing oilfield production and injection and a preparation method thereof. Background Art

[0002] The main role of surfactants in enhanced oil recovery is to reduce the interfacial tension between the displacement fluid and crude oil and improve the wettability of the reservoir. Surfactants have both oleophilic (hydrophobic) and hydrophilic (oleophobic) properties. When surfactants are dissolved in water, the molecules are mainly adsorbed on the oil-water interface, which can significantly reduce the oil-water interfacial tension.

[0003] The existing biosurfactants have poor oil recovery and production increase efficiency, and the product's pressure reduction and injection increase efficiency is low, making it difficult to achieve coordinated improvements in oil recovery and production increase, pressure reduction and injection increase. At the same time, the product has poor stability. In a high-temperature and acidic environment, the product performance deteriorates significantly, limiting the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a mesophase biosurfactant for increasing oil field production and injection and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a mesophase biosurfactant for increasing oilfield production and injection, wherein the mesophase biosurfactant comprises the following raw materials in parts by weight:

[0007] 15-20 parts of composite surfactant, 5-8 parts of continuous adjustment and feeding agent, 2-4 parts of silane coupling agent, 1-3 parts of Tween 80, 3-6 parts of glass fiber modified graphene agent, and 20-25 parts of water.

[0008] The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:2.

[0009] Preferably, the biosurfactant is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document No. CN108559473B; and the silane coupling agent is silane coupling agent KH560.

[0010] Preferably, the preparation method of the continuous adjustment and feeding agent is:

[0011] S01: The nano-mica powder is first heated to 155-165°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 235-245°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to room temperature;

[0012] S02: 8 to 10 parts of the nano-mica powder of S01 are first added to 15 to 20 parts of sodium dodecylbenzene sulfonate solution, and then 4 to 8 parts of phosphate buffer solution with a pH value of 5.0 and 1 to 3 parts of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent;

[0013] S03: adding 2 to 4 parts of yttrium nitrate solution and 1 to 3 parts of urea to 10 to 15 parts of sodium alginate solution, and then adding 1 to 2 parts of wollastonite and mixing them thoroughly to obtain a continuous adjustment modified solution;

[0014] S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

[0015] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 10-15%.

[0016] Preferably, the stirring speed of the stirring modification treatment is 350 to 400 r / min, and the stirring time is 20 to 30 min.

[0017] Preferably, the preparation method of the graphene agent based on glass fiber modification is:

[0018] S101: heat treating the graphene at 155-175°C for 10-15 min, then heating it to 255-260°C at a rate of 2-4°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature;

[0019] The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent;

[0020] S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

[0021] Preferably, the preparation method of the glass fiber liquid is:

[0022] The glass fiber is first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 300 to 350 W. After the irradiation is completed, 4 to 7 parts of irradiated glass fiber and 1 to 2 parts of stearic acid are blended and added into 6 to 10 parts of chitosan solution, and finally 2 to 3 parts of hydroxyapatite and 2 to 4 parts of lanthanum nitrate solution are added, and the mixture is blended and stirred. After the stirring is completed, a glass fiber solution is obtained.

[0023] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-7%.

[0024] Preferably, the mixing and stirring process has a stirring speed of 450 to 650 r / min, a stirring time of 30 to 40 min, and a stirring temperature of 50 to 55°C.

[0025] The present invention also provides a method for preparing a mesophase biosurfactant for increasing oilfield production and injection, comprising the following steps:

[0026] The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The biosurfactant of the present invention adopts a composite surfactant in combination with a silane coupling agent and Tween 80, and a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added at the same time. The two are coordinated and work together to obtain a surfactant that can achieve coordinated improvement in oil production, pressure reduction and injection increase of the product, and the product has excellent stability in a high temperature and acid corrosion environment;

[0029] 2. The continuous adjustment and continuous feeding agent adopts nano mica powder, firstly heats up to 155-165°C at a rate of 2-5°C / min, keeps warm for 5-10min, then heats up to 235-245°C at a rate of 1-3°C / min, and keeps warm for 2-5min. The active efficiency of the nano mica powder is improved by continuous thermal improvement and optimization of the nano mica powder. The sodium dodecylbenzene sulfonate solution, the phosphate buffer solution with a pH value of 5.0, and the carboxymethyl cellulose are blended and ball-milled. The coordination and coordination between the raw materials are used to optimize the coordination and synergistic effect of the pre-adjusted nano mica agent and the continuous adjustment and modification liquid, so that the continuous adjustment and modification liquid can better improve the nano mica powder. The continuous adjustment and modification liquid adopts yttrium nitrate solution, urea, sodium alginate solution and wollastonite to be fully blended to obtain the continuous adjustment and modification liquid.

[0030] 3. By adjusting the raw materials in the continuous adjustment and modification liquid, the needle-shaped wollastonite is interspersed with the nano-mica powder, and the interlayer spacing structure of the nano-mica powder is interspersed in the system, and the raw materials in the continuous adjustment and modification liquid are coordinated and improved by the adjustment and improvement of the raw materials, the continuous adjustment and continuous feeding agent in the product is enhanced in terms of oil production, production increase, pressure reduction and injection increase, and the product has excellent stability in high temperature and acid corrosion environment;

[0031] 4. The graphene agent based on glass fiber modification uses graphene to be heat-treated at 155-175°C for 10-15 minutes, then heated to 255-260°C at a rate of 2-4°C / min, kept warm for 5 minutes, and finally air-cooled to room temperature to optimize the activity of graphene, and then immersed in a sodium silicate solution to improve the coordination and addition effect of graphene and glass fiber liquid;

[0032] 5. The glass fiber liquid is irradiated in a proton irradiation box before the glass fiber is irradiated to optimize the activity performance of the glass fiber. Stearic acid, chitosan solution, hydroxyapatite and lanthanum nitrate solution are then used. Glass fiber is combined with hydroxyapatite and other raw materials to coordinate and improve the graphene raw materials, enhance the synergistic effect of the glass fiber-modified graphene agent and the continuous adjustment and feeding agent, and further coordinate and improve the product's oil production, increase production, reduce pressure and increase injection effects. At the same time, the product has excellent stability in high temperature and acid corrosion environment. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present embodiment provides a mesophase biosurfactant for increasing oilfield production and injection, wherein the mesophase biosurfactant comprises the following raw materials in parts by weight:

[0035] 15-20 parts of composite surfactant, 5-8 parts of continuous adjustment and feeding agent, 2-4 parts of silane coupling agent, 1-3 parts of Tween 80, 3-6 parts of glass fiber modified graphene agent, and 20-25 parts of water.

[0036] The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:2.

[0037] Preferably, the biosurfactant is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document No. CN108559473B; and the silane coupling agent is silane coupling agent KH560.

[0038] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:

[0039] S01: The nano-mica powder is first heated to 155-165°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 235-245°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to room temperature;

[0040] S02: 8 to 10 parts of the nano-mica powder of S01 are first added to 15 to 20 parts of sodium dodecylbenzene sulfonate solution, and then 4 to 8 parts of phosphate buffer solution with a pH value of 5.0 and 1 to 3 parts of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent;

[0041] S03: adding 2 to 4 parts of yttrium nitrate solution and 1 to 3 parts of urea to 10 to 15 parts of sodium alginate solution, and then adding 1 to 2 parts of wollastonite and mixing them thoroughly to obtain a continuous adjustment modified solution;

[0042] S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

[0043] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 10-15%.

[0044] The stirring speed of the stirring modification treatment in this embodiment is 350-400 r / min, and the stirring is 20-30 min.

[0045] The preparation method of the glass fiber modified graphene agent of this embodiment is:

[0046] S101: heat treating the graphene at 155-175°C for 10-15 min, then heating it to 255-260°C at a rate of 2-4°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature;

[0047] The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent;

[0048] S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

[0049] The preparation method of the glass fiber liquid of this embodiment is:

[0050] The glass fiber is first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 300 to 350 W. After the irradiation is completed, 4 to 7 parts of irradiated glass fiber and 1 to 2 parts of stearic acid are blended and added into 6 to 10 parts of chitosan solution, and finally 2 to 3 parts of hydroxyapatite and 2 to 4 parts of lanthanum nitrate solution are added, and the mixture is blended and stirred. After the stirring is completed, a glass fiber solution is obtained.

[0051] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-7%.

[0052] The stirring speed of the blending and stirring process in this embodiment is 450-650 r / min, the stirring time is 30-40 min, and the stirring temperature is 50-55°C.

[0053] The method for preparing a mesophase biosurfactant for increasing oilfield production and injection in this embodiment comprises the following steps:

[0054] The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

[0055] Example 1.

[0056] The present embodiment provides a mesophase biosurfactant for increasing oilfield production and injection, wherein the mesophase biosurfactant comprises the following raw materials in parts by weight:

[0057] 15 parts of composite surfactant, 5 parts of continuous adjustment and feeding agent, 2 parts of silane coupling agent, 1 part of Tween 80, 3 parts of glass fiber modified graphene agent, and 20 parts of water.

[0058] The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:2.

[0059] The biosurfactant of this embodiment is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document number CN108559473B; the silane coupling agent is silane coupling agent KH560.

[0060] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:

[0061] S01: The nano-mica powder was heated to 155°C at a rate of 2°C / min, kept at this temperature for 5 minutes, then heated to 235°C at a rate of 1°C / min, kept at this temperature for 2 minutes, and finally cooled to room temperature in air;

[0062] S02: 8 parts of the nano-mica powder of S01 are first added to 15 parts of sodium dodecylbenzene sulfonate solution, and then 4 parts of phosphate buffer solution with a pH value of 5.0 and 1 part of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent;

[0063] S03: adding 2 parts of yttrium nitrate solution and 1 part of urea to 10 parts of sodium alginate solution, and then adding 1 part of wollastonite and mixing thoroughly to obtain a continuous adjustment modified solution;

[0064] S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

[0065] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 10%.

[0066] The stirring speed of the stirring modification treatment in this embodiment is 350 r / min, and the stirring is performed for 20 min.

[0067] The preparation method of the glass fiber modified graphene agent of this embodiment is:

[0068] S101: heat treating the graphene at 155°C for 10 min, then heating it to 255°C at a rate of 2°C / min, keeping it at that temperature for 5 min, and finally air cooling it to room temperature;

[0069] The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent;

[0070] S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

[0071] The preparation method of the glass fiber liquid of this embodiment is:

[0072] The glass fiber was first irradiated in a proton irradiation box for 5 minutes with an irradiation power of 300 W. After the irradiation was completed, 4 parts of irradiated glass fiber and 1 part of stearic acid were blended and added to 6 parts of chitosan solution. Finally, 2 parts of hydroxyapatite and 2 parts of lanthanum nitrate solution were added and mixed and stirred. After the stirring was completed, a glass fiber solution was obtained.

[0073] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the lanthanum nitrate solution is 4%.

[0074] The stirring speed of the blending and stirring process in this embodiment is 450 r / min, the stirring time is 30 min, and the stirring temperature is 50°C.

[0075] The method for preparing a mesophase biosurfactant for increasing oilfield production and injection in this embodiment comprises the following steps:

[0076] The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

[0077] Example 2.

[0078] The present embodiment provides a mesophase biosurfactant for increasing oilfield production and injection, wherein the mesophase biosurfactant comprises the following raw materials in parts by weight:

[0079] 20 parts of composite surfactant, 8 parts of continuous adjustment and feeding agent, 4 parts of silane coupling agent, 3 parts of Tween 80, 6 parts of glass fiber modified graphene agent, and 25 parts of water.

[0080] The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:2.

[0081] The biosurfactant of this embodiment is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document number CN108559473B; the silane coupling agent is silane coupling agent KH560.

[0082] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:

[0083] S01: The nano-mica powder was heated to 165°C at a rate of 5°C / min, kept at this temperature for 10 minutes, then heated to 245°C at a rate of 3°C / min, kept at this temperature for 5 minutes, and finally cooled to room temperature in air;

[0084] S02: 10 parts of the nano-mica powder of S01 are first added to 20 parts of sodium dodecylbenzene sulfonate solution, and then 8 parts of phosphate buffer solution with a pH value of 5.0 and 3 parts of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent;

[0085] S03: adding 4 parts of yttrium nitrate solution and 3 parts of urea to 15 parts of sodium alginate solution, and then adding 2 parts of wollastonite and mixing thoroughly to obtain a continuous adjustment modified solution;

[0086] S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

[0087] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 15%.

[0088] The stirring speed of the stirring modification treatment in this embodiment is 400 r / min, and the stirring is for 30 minutes.

[0089] The preparation method of the glass fiber modified graphene agent of this embodiment is:

[0090] S101: heat treating the graphene at 175°C for 15 min, then heating it to 260°C at a rate of 4°C / min, keeping it at that temperature for 5 min, and finally air cooling it to room temperature;

[0091] The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent;

[0092] S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

[0093] The preparation method of the glass fiber liquid of this embodiment is:

[0094] The glass fiber was first irradiated in a proton irradiation box for 10 minutes with an irradiation power of 350W. After the irradiation was completed, 7 parts of irradiated glass fiber and 2 parts of stearic acid were blended and added to 10 parts of chitosan solution. Finally, 3 parts of hydroxyapatite and 4 parts of lanthanum nitrate solution were added and mixed and stirred. After the stirring was completed, a glass fiber solution was obtained.

[0095] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the lanthanum nitrate solution is 7%.

[0096] The stirring speed of the blending and stirring process in this embodiment is 650 r / min, the stirring time is 40 min, and the stirring temperature is 55°C.

[0097] The method for preparing a mesophase biosurfactant for increasing oilfield production and injection in this embodiment comprises the following steps:

[0098] The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

[0099] Example 3.

[0100] The present embodiment provides a mesophase biosurfactant for increasing oilfield production and injection, wherein the mesophase biosurfactant comprises the following raw materials in parts by weight:

[0101] 17.5 parts of composite surfactant, 6.5 parts of continuous adjustment and feeding agent, 3 parts of silane coupling agent, 2 parts of Tween 80, 4.5 parts of glass fiber modified graphene agent, and 22.5 parts of water.

[0102] The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:2.

[0103] The biosurfactant of this embodiment is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document number CN108559473B; the silane coupling agent is silane coupling agent KH560.

[0104] The preparation method of the continuous adjustment and continuous feeding agent of this embodiment is:

[0105] S01: The nano-mica powder was first heated to 160°C at a rate of 3.5°C / min, kept at this temperature for 7.5 min, then heated to 240°C at a rate of 2°C / min, kept at this temperature for 3.5 min, and finally cooled to room temperature in air;

[0106] S02: 9 parts of the nano-mica powder of S01 are first added to 17.5 parts of sodium dodecylbenzene sulfonate solution, and then 6 parts of phosphate buffer solution with a pH value of 5.0 and 2 parts of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent;

[0107] S03: adding 3 parts of yttrium nitrate solution and 2 parts of urea to 12.5 parts of sodium alginate solution, and then adding 1.5 parts of wollastonite and blending thoroughly to obtain a continuous modified solution;

[0108] S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

[0109] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 12.5%.

[0110] The stirring speed of the stirring modification treatment in this embodiment is 370 r / min, and the stirring is 25 min.

[0111] The preparation method of the glass fiber modified graphene agent of this embodiment is:

[0112] S101: The graphene is first heat treated at 160°C for 12.5 min, then heated to 257°C at a rate of 3°C / min, kept at this temperature for 5 min, and finally air-cooled to room temperature;

[0113] The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent;

[0114] S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

[0115] The preparation method of the glass fiber liquid of this embodiment is:

[0116] The glass fiber was first irradiated in a proton irradiation box for 7.5 minutes at an irradiation power of 320 W. After the irradiation was completed, 5.5 parts of the irradiated glass fiber and 1.5 parts of stearic acid were blended and added to 8 parts of chitosan solution. Finally, 2.5 parts of hydroxyapatite and 3 parts of lanthanum nitrate solution were added, and the mixture was blended and stirred. After the stirring was completed, a glass fiber solution was obtained.

[0117] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the lanthanum nitrate solution is 5.5%.

[0118] The stirring speed of the blending and stirring process in this embodiment is 500 r / min, the stirring time is 35 min, and the stirring temperature is 52°C.

[0119] The method for preparing a mesophase biosurfactant for increasing oilfield production and injection in this embodiment comprises the following steps:

[0120] The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

[0121] Comparative Example 1.

[0122] The difference from Example 3 is that no continuous adjustment and feeding agent is added.

[0123] Comparative Example 2.

[0124] The difference from Example 3 is that step S01 is not used in the preparation of the continuous adjustment and continuous feeding agent.

[0125] Comparative Example 3.

[0126] The difference from Example 3 is that the pre-adjusted nano-mica agent in the preparation of the continuous adjustment and continuous feeding agent is replaced by nano-mica powder.

[0127] Comparative Example 4.

[0128] The difference from Example 3 is that the continuous adjustment of the modified liquid treatment is not adopted.

[0129] Comparative Example 5.

[0130] The difference from Example 3 is that no yttrium nitrate solution and urea are added in the preparation of the continuous adjustment and modification solution.

[0131] Comparative Example 6.

[0132] The difference from Example 3 is that wollastonite is not added in the preparation of the continuous adjustment and modification liquid.

[0133] Comparative Example 7.

[0134] The difference from Example 3 is that no glass fiber-modified graphene agent is added.

[0135] Comparative Example 8.

[0136] The difference from Example 3 is that the graphene agent immersed in the preparation of the glass fiber-modified graphene agent is replaced by graphene raw material.

[0137] Comparative Example 9.

[0138] The difference from Example 3 is that glass fiber liquid treatment is not used in the preparation of the graphene agent based on glass fiber modification.

[0139] The product performance of Examples 1-3 and Comparative Examples 1-9 was tested, and the pressure reduction rate was tested using the Q / SH10202252-2019 test method. The products were placed at 65°C for 24 hours, and then placed under 2% hydrochloric acid mist for 24 hours. The high temperature resistance and acid corrosion stability of the products were then tested. The performance measurement results are as follows

[0140]

[0141]

[0142] It can be concluded from Examples 1-3 and Comparative Examples 1-9 that

[0143] The product of Example 3 of the present invention has excellent crude oil recovery rate and pressure reduction rate under conventional conditions, and also has excellent crude oil recovery rate and pressure reduction rate under high temperature and acid corrosion conditions;

[0144] From Comparative Examples 1-9 and Example 3, it can be seen that the product does not add a continuous adjustment and feeding agent, and does not add one of the graphene agents based on glass fiber modification, and the performance of the product deteriorates significantly. The performance effect of the product is most significant when the two are coordinated and work together.

[0145] The performance of the product showed a trend of deterioration when the S01 step was not used in the preparation of the continuous adjustment and continuous feeding agent, the pre-adjusted nano-mica agent was replaced by nano-mica powder in the preparation of the continuous adjustment and continuous feeding agent, and the continuous adjustment and modification liquid was not used for treatment. At the same time, yttrium nitrate solution, urea, and wollastonite were not added in the preparation of the continuous adjustment and modification liquid, and the performance of the product also showed a trend of deterioration. The continuous adjustment and continuous feeding agent obtained by the continuous adjustment and modification liquid obtained by the method of the present invention and the specific process of the present invention had the most significant performance effect of the product. The replacement by other methods was not as obvious as the effect of the present invention.

[0146] In the preparation of the glass fiber modified graphene agent, the graphene agent immersed is replaced by graphene raw material, and in the preparation of the glass fiber modified graphene agent, glass fiber liquid treatment is not used. The performance of the product also shows a trend of deterioration, especially without glass fiber liquid treatment. The performance of the product deteriorates more significantly. The glass fiber modified graphene agent obtained by the method of the present invention has the most significant product performance effect.

[0147] As the glass fiber liquid treatment has a significant impact on the performance of the product, further research is conducted on this:

[0148] The preparation method of glass fiber liquid is as follows:

[0149] The glass fiber was first irradiated in a proton irradiation box for 7.5 minutes at an irradiation power of 320 W. After the irradiation was completed, 5.5 parts of the irradiated glass fiber and 1.5 parts of stearic acid were blended and added to 8 parts of chitosan solution. Finally, 2.5 parts of hydroxyapatite and 3 parts of lanthanum nitrate solution were added, and the mixture was blended and stirred. After the stirring was completed, a glass fiber solution was obtained.

[0150] Experimental example 1.

[0151] The only difference from Example 3 is that hydroxyapatite is not added in the preparation of the glass fiber liquid.

[0152] Experimental example 2.

[0153] The only difference from Example 3 is that no lanthanum nitrate solution is added in the preparation of the glass fiber liquid.

[0154] Experimental Example 3.

[0155] The only difference from Example 3 is that no irradiated glass fibers are added in the preparation of the glass fiber liquid.

[0156] Experimental Example 4.

[0157] The same as Example 3, the only difference is that the chitosan solution is replaced by deionized water.

[0158]

[0159]

[0160] It can be seen from Experimental Examples 1-4 that when irradiated glass fibers were not added in the preparation of the glass fiber liquid, the performance of the product deteriorated significantly. At the same time, when hydroxyapatite was not added in the preparation of the glass fiber liquid, lanthanum nitrate solution was not added in the preparation of the glass fiber liquid, and deionized water was used instead of the chitosan solution, the performance of the products tended to deteriorate. The glass fiber liquid obtained by the specific method of the present invention had the most significant product performance effect, and other methods were not as significant as the effect of the present invention.

[0161] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0162] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A mesophase biosurfactant for increasing oilfield production and injection, characterized in that: The mesophase biosurfactant comprises the following raw materials in parts by weight: 15-20 parts of composite surfactant, 5-8 parts of continuous adjustment and feeding agent, 2-4 parts of silane coupling agent, 1-3 parts of Tween 80, 3-6 parts of glass fiber modified graphene agent, and 20-25 parts of water. The composite surfactant is prepared by mixing alkyl sulfobetaine, sodium dodecyl diphenyl ether disulfonate and a biosurfactant in a weight ratio of 1:1:

2.

2. The mesophase biosurfactant for increasing oilfield production and injection according to claim 1, characterized in that: The biosurfactant is a lipopeptide biosurfactant, which is prepared by referring to the lipopeptide biosurfactant method in Chinese patent document number CN108559473B; the silane coupling agent is silane coupling agent KH560.

3. The mesophase biosurfactant for increasing oilfield production and injection according to claim 2, characterized in that: The preparation method of the continuous adjustment and continuous feeding agent is: S01: The nano-mica powder is first heated to 155-165°C at a rate of 2-5°C / min, kept at this temperature for 5-10 minutes, then heated to 235-245°C at a rate of 1-3°C / min, kept at this temperature for 2-5 minutes, and finally air-cooled to room temperature; S02: 8 to 10 parts of the nano-mica powder of S01 are first added to 15 to 20 parts of sodium dodecylbenzene sulfonate solution, and then 4 to 8 parts of phosphate buffer solution with a pH value of 5.0 and 1 to 3 parts of carboxymethyl cellulose are added for blending and ball milling. After the ball milling is completed, the mixture is washed with water and dried to obtain a pre-adjusted nano-mica agent; S03: adding 2 to 4 parts of yttrium nitrate solution and 1 to 3 parts of urea to 10 to 15 parts of sodium alginate solution, and then adding 1 to 2 parts of wollastonite and mixing them thoroughly to obtain a continuous adjustment modified solution; S04: The pre-adjusted nano-mica agent and the continuous adjustment and modification liquid are stirred and modified in a weight ratio of 3:

5. After the stirring is completed, the mixture is washed with water and dried to obtain a continuous adjustment and continuous feeding agent.

4. The mesophase biosurfactant for increasing oilfield production and injection according to claim 3, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 10-15%.

5. The mesophase biosurfactant for increasing oilfield production and injection according to claim 3, characterized in that: The stirring speed of the stirring modification treatment is 350-400 r / min, and the stirring is 20-30 minutes.

6. The mesophase biosurfactant for increasing oilfield production and injection according to claim 1, characterized in that: The preparation method of the graphene agent based on glass fiber modification is: S101: heat treating the graphene at 155-175°C for 10-15 min, then heating it to 255-260°C at a rate of 2-4°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature; The graphene cooled to room temperature is immersed in a sufficient amount of sodium silicate solution with a mass fraction of 10% for immersion treatment, and after the immersion is completed, the graphene is filtered and dried to obtain an immersed graphene agent; S102: The immersed graphene agent and glass fiber liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a graphene agent based on glass fiber modification.

7. The mesophase biosurfactant for increasing oilfield production and injection according to claim 6, characterized in that: The preparation method of the glass fiber liquid is: The glass fiber is first irradiated in a proton irradiation box for 5 to 10 minutes with an irradiation power of 300 to 350 W. After the irradiation is completed, 4 to 7 parts of irradiated glass fiber and 1 to 2 parts of stearic acid are blended and added into 6 to 10 parts of chitosan solution, and finally 2 to 3 parts of hydroxyapatite and 2 to 4 parts of lanthanum nitrate solution are added, and the mixture is blended and stirred. After the stirring is completed, a glass fiber solution is obtained.

8. The mesophase biosurfactant for increasing oilfield production and injection according to claim 7, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum nitrate solution is 4-7%.

9. The mesophase biosurfactant for increasing oilfield production and injection according to claim 7, characterized in that: The mixing and stirring process has a stirring speed of 450-650 r / min, a stirring time of 30-40 min, and a stirring temperature of 50-55° C.

10. A method for preparing a mesophase biosurfactant for increasing oil field production and injection as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The composite surfactant and Tween 80 are added into water, and then a silane coupling agent, a continuous adjustment and feeding agent and a graphene agent based on glass fiber modification are added, and the mixture is mechanically stirred and mixed thoroughly to obtain the intermediate phase biosurfactant for increasing oil field production and injection of the present invention.

Citation Information

Patent Citations

  • A biosurfactant-containing water injection well depressurizing and injection enhancing agent

    CN108559473B